Revisiting net neutrality from a polycentric perspective: Brazilian and German scenarios - Nathalia Sautchuk-Patrício (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2022)
In the various arenas of the Internet Governance debate, one of the points frequently highlighted is the need the need to maintain an 'open Internet'. Despite the common use of the term, which can be understood as a synonym for net neutrality, its meaning varies amongst the diverse cast of stakeholders. Internet governance can be seen as a polycentric mode of governance since the discussion takes place in different arenas and at varying levels. Moreover, these operate not exclusively in separate, individual ways but are connected through regulatory networks. Generally, polycentric governance contains three distinct structural layers to order dynamics: norms, practices and underlying orders. Also, this mode of governance manifests seven main attributes: trans-scalarity, trans-sectorality, diffusion, fluidity, over-lapping mandates, ambiguous hierarchies and the absence of a final arbiter. This text will revisit the net neutrality debate through a polycentric perspective, not used before to analyse this topic, as an approach to highlight some aspects of this discussion that were neglected in previous research.
urn:nbn:de:hbz:465-20220926-104551-9
Keywords: 320; Internet governance; polycentric governance; net neutrality